Polymer Engineering - Constantí, Magda; Garcia-Valls, Ricard; Gavilà, Llorenç; Güell, Edgar; Jastrzab, Renata; Koroniak; Marciniak, Lukasz; Maru, Biniam T.; Medina, Francesc; Nogalska, Adrianna; Nowak, Martyna; Runka, Tomasz; et al. (De Gruyter, 2017)
Polymer Engineering focuses on the preparation and application of polymers in several hot topics such as artificial photosynthesis, water purification by membrane technologies, and biodiesel production from wastewater plants. The authors not only describe the latest developments in polymer science, but also support these experimental results by computational chemistry and modelling studies.